High prevalence of fatty liver and its association with metabolic syndrome among rural adults with chronic hepatitis C: Implications for primary healthcare - Ta-Jen Wang; Mei-Yen Chen; Yu-Chih Lin; Wen-Nan Chiu; Tung-Jung Huang; Hsu-Huei Weng (BMC, 2024)
Abstract Background Chronic hepatitis C (CHC) virus infection is a global health concern that is associated with significant liver-related morbidity and mortality. Owing to the inflammatory pathway, CHC can causefatty liver, liver cirrhosis, and liver cancer and is associated with cardiometabolic diseases, such as hypertension and diabetes. Fatty liver is associated with metabolic disorders, cardiovascular diseases, diabetes, and liver cancer. Hence, the early detection of fatty liver through noninvasive screening in adults with CHC is important in primary healthcare settings. This study aimed to explore the prevalence of fatty liver and its association with metabolic syndrome amongrural adults with CHC. Methods This was a series of cohort studies related to the elimination of the CHC burden around the western coastal Yunlin County, Taiwan, between August 2018 and July 2021. A cross-sectional study was conducted after hepatitis C virus RNA confirmation in a hepatitis C- endemic area. A gastrointestinal physician or radiologist assessed fatty liver by ultrasonography. Fatty liver was classified into four grades: normal, mild, moderate, and severe. Three liver enzyme biomarkers were identified. According to the Taiwan national standard, metabolic syndrome was defined based on the presence of three or more of the five abnormal biomarkers, including increased waist circumference, elevated blood pressure, elevated fasting blood glucose level, elevated triglyceride level, and low high-density lipoprotein cholesterol level. Results A total of 256 rural adults with CHC were enrolled. The mean age of the participants was 67.5 (standard deviation = 11.8) years, with a low educational level. High prevalence of fatty liver (79%), central obesity (54.3%), elevated blood pressure (55.5%),elevated fasting blood glucose (FBG) level (44.9%), and metabolic syndrome (37.9%) were observed.The results showed that adults with CHC with moderate to severe fatty liver were significantly associated with an increased risk of increased waist circumference (P < 0.001), increased blood pressure (P < 0.001), low high-density lipoprotein cholesterol level (P < 0.05), and elevated liver enzyme biomarker levels (all P < 0.05) after adjusting for age, sex, and educational level. Furthermore, adults with CHC with moderate to severe fatty liver were significantly associated with a greater risk of metabolic syndrome (odds ratio = 2.85, 95% confidence interval = 1.66 to 4.92). Conclusions The findings demonstrate a high prevalence of fatty liver in rural adults with CHC, which is significantly associated with obesity, metabolic syndrome, and elevated liver biomarker levels. Clinicians and primary healthcare providers must encourage patients with CHC to receive antiviral therapy combined with weight loss management and lifestyle modification, allowing general improvements in their liver and cardiometabolic health.